Gamers at work: Predicting workplace-relevant behaviours across domains. Issue 2 (1st September 2019) - Short, Elizabeth; Weidner, Nathan
Active gamers are increasingly making up a larger portion of the modern workforce. In response to this, organizations have sought to gamify various workplace practices. This has even begun to include the use of assessment games for employee recruitment and selection. One important limitation of using games for assessment purposes may be the cross-domain generalizability of behaviours between game and workplace contexts. World of Warcraft players (N = 355) responded to an online survey to examine the cross-domain generalizability of important workplace constructs including prosocial organizational citizenship behaviours, aggressive counterproductive workplace behaviours and domain-specific goal orientations. Results indicate that there are moderate correlations between self-reported in-game behaviours and self-reported work behaviours. Furthermore, in-game constructs typically showed similar relationships with in-game performance as the workplace constructs do with job performance.